Pengaruh Pengawasan Dan Keselamatan Kerja Terhadap Produktivitas Kerja Karyawan Pt. Pinago Utama Tbk Musi Banyuasin - Rafelinda, Vira; Hendri, Edduar; Novalia, Nurkardina (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine whether there is an effect of supervision on employee work productivity, whether there is an influence of work safety on employee work productivity, and whether there is an effect of supervision and work safety on employee work productivity at PT. Pinago Utama Tbk Musi Banyuasin. The population in this study were field and production employees at PT. Pinago Utama Tbk Musi Banyuasin, totaling 60 people. The research sample was determined using purvosive sampling, namely determining the sample with certain considerations and calculated using the slovin formula. Data analysis techniques using the classical assumption test, multiple linear regression analysis, the coefficient of determination, and hypothesis testing. The results of this study show that, first, supervision does not have a positive and significant effect on the work productivity of employees at PT. Pinago Utama Tbk Musi Banyuasin. Second, work safety has no positive and significant effect on employee work productivity at PT. Pinago Utama Tbk Musi Banyuasin. The three supervision and work safety do not have a positive and significant effect on the work productivity of employees at PT. Pinago Utama Tbk Musi Banyuasin. Keywords : Supervision, Work Safety, Employee